A contribution to the Slovenian spider fauna – I. - Rok Kostanjšek (Natura Sloveniae)
Sixteen spider species, new to the Slovenian fauna, have been recorded: Aphantaulax trifasciata, Araneus triguttatus, Arctosa cinerea, Cnephalocotes obscurus, Helophora insignis, Heriaeus hirtus, Nomisia exornata, Nurscia albomaculata, Pardosa agricola, Pardosa prativaga, Pardosa proxima, Philodromus longipalpis, Runcinia grammica, Theridula gonygaster, Xysticus ninnii and Zora armillata. Recent records on presumably extinct endemic species Nesticus idriacus are also provided, as well as suggestion to its transfer to the IUCN category rare (R).